2022
DOI: 10.1080/07370008.2022.2118279
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-dimensional Framework for Documenting Students’ Heterogeneous Experiences with Programming Bugs

Abstract: When teachers, researchers, and students describe productively responding to moments of failure in the learning process, what might this mean? Blending prior theoretical and empirical research on the relationship between failure and learning, and empirical results from four data sets that are part of a larger design-based research project, we investigate the heterogeneous processes teachers and students value and pursue following moments in which computer bugs thwart their immediate progress on an activity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 104 publications
0
0
0
Order By: Relevance
“…In other moments, I saw her invite a child who made an error to promptly ask for assistance from a peer, while at times, she would just provide the right answer herself. These sorts of variations mirror work by DeLiema et al (2023), who observed that teachers employed multiple approaches when learners made mistakes, at times electing to give students the right answer and at other occasions giving them strategies to correct themselves.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In other moments, I saw her invite a child who made an error to promptly ask for assistance from a peer, while at times, she would just provide the right answer herself. These sorts of variations mirror work by DeLiema et al (2023), who observed that teachers employed multiple approaches when learners made mistakes, at times electing to give students the right answer and at other occasions giving them strategies to correct themselves.…”
Section: Discussionmentioning
confidence: 57%
“…This wide variation in strategies within a single classroom illustrates this teacher's adaptiveness as she strives to individualize her responses based on the children's performance, learning needs, and behaviors-often an explicit goal of Kindergarten teachers (Donaldson, 2019a). Instructional variations like these have been illustrated in other work (e.g., Bray, 2011;Donaldson, 2021;DeLiema et al, 2023) but are not always the main focus of research on feedback and learning from mistakes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation